Effects of the STRIP dietary intervention on blood cell transcriptome and activity of signaling pathways - Rikkinen, Janette (My University, 2023)
Atherosclerotic cardiovascular diseases (CVDs) are the largest group of diseases causing deaths. CVD risk may be reduced with following the dietary and other lifestyle recommendations. Diet can affect gene expression both at an individual gene and molecular pathway levels. The STRIP study (Special Turku Coronary Risk Factor Intervention Project) is a dietary intervention, where intervention group received repeated and individualized dietary counselling from 0.7 to 20 years of age, targeting to reduce CVD risk factor levels by replacing saturated fatty acids (SAFAs) with unsaturated fat in diet. Aims of the thesis was to find out, if SAFA intake of total energy intake (SAFA E%) has an effect on blood cell transcriptome measured both at individual gene and pathway levels. Parts from pre-collected longitudinal clinical data from the STRIP study data were used to match with blood transcriptome data from 495 STRIP participants (age 15–19 years) including mRNA- sequencing counts for 25562 genes. Clinical data were managed and analyzed with SAS. DESeq2 package in R software was used for differential gene expression (DGE) analysis which was adjusted with age, sex, and mRNA-sequencing batch. Molecular pathway enrichment analysis was conducted with two different methods (GOseq and edgeR R packages). Benjamin- Hochberg’s adjusted p-value <0.05 was used to determine the statistical significance. 64 upregulated and 10 downregulated genes were found in DGE analysis using continuous SAFA E% as a predictor variable. The two molecular pathway enrichment analyses resulted one upregulated (membrane biogenesis) and two downregulated (immunoglobulin complex and spermatogenesis) pathways when SAFA E% increases. In conclusion, the results of this thesis suggest that relative intake of dietary saturated fat affects gene expression in whole blood at both individual gene and pathway levels. Most of the results supported the prior literature, but also novel results possibly associated with cardiovascular health were observed. However, further studies are needed to establish their role in heart health.

Ateroskleroottiset sydän- ja verisuonitaudit (CVD) ovat suurin kuolemia aiheuttava sairauksien ryhmä. Ateroskleroosin kehittymistä voi ehkäistä noudattamalla terveellisiä elämäntapoja. Ruo- kavalio voi vaikuttaa yksilön yksittäisten geenien ilmentymiseen ja siten myös signalointireittien aktiivisuuteen. STRIP (SepelvaltimoTaudin Riskitekijöiden InterventioProjekti) on interven- tiotutkimus, missä interventioryhmän osallistujat saivat yksilöllistä ravintoneuvontaa 0.7 vuoden iästä 20 ikävuoteen saakka tavoitteena vähentää CVD-riskitekijöiden tasoja korvaamalla tyydyt- tyneiden rasvojen (SAFA) käyttöä tyydyttymättömillä rasvoilla. Tutkielman tavoitteena oli sel- vittää, vaikuttaako SAFA:n osuus kokonaisenergian saannista (E%) verisolujen transkriptomiin sekä yksittäisten geenien että molekyylireittien tasolla. Tutkielman tekemisessä käytettiin osia STRIP-tutkimuksen aikana kerätystä kliinisestä datasta, sekä verinäytteestä analysoitua lähetti-RNA-sekvensointidataa. Mukana oli 495 15–19-vuotiasta STRIP-osallistujaa sekä geenitoiminnan tasot 25 562 geenistä. Kliininen data muokattiin ja ana- lysoitiin SAS-ohjelmistolla. R-ohjelmiston DESeq2-pakettia käytettiin analysoimaan SAFA E%:n yhteyksiä veren geeni-ilmentymään (nk. differentiaaliseen geeniekspressio; DGE). DGE- analyysi vakioitiin iän, sukupuolen ja sekvensointierän mukaan. Molekyylireittien aktiivisuutta testattiin kahdella eri analyysimenetelmällä (GOseq- ja edgeR -ohjelmistopaketit). Benjamini– Hochbergin korjattu p-arvo <0.05 määritti tilastollisen merkitsevyyden. Kun jatkuvaa SAFA E% muuttujaa käytettiin DGE-analyysissä, tulokset osoittivat 64 geenin ilmentymisen lisääntyneen ja 10 geenin ilmentymisen vähentyneen. Molekyylireittien aktiivisuusanalyyseistä löytyi yksi reitti (solukalvon biogeneesi), jonka aktiivisuus lisääntyy ja kaksi reittiä (immunoglobuliinikompleksi ja spermatogeneesi), joiden aktiivisuus vähenee SAFA E% kasvaessa. Yhteenvetona, tämän tutkielman tulokset viittaavat ravinnon tyydyttyneiden rasvahappojen suh- teellisen osuuden vaikuttavan kokoveren geenien ilmentymiseen sekä yksittäisten geenien että molekyylireittien tasoilla. Suurin osa tutkielman tuloksista tukee aikaisempaa kirjallisuutta, mutta osa tuloksista on uusia ilman aiempia yhteyksiä sydänterveyteen. Tarvitaan kuitenkin lisätutki- muksia, jotta uusien tulosten tarkempi yhteys sydänterveyteen voidaan varmentaa.
Keywords: atherosclerosis, blood cell transcriptome, CVD, differential gene expression, mRNA-seq, pathway enrichment analysis, SAFA